2020
DOI: 10.1371/journal.pone.0237580
|View full text |Cite
|
Sign up to set email alerts
|

Risks of requiring a dedicated molecular specimen for HIV diagnosis and a potential strategy for mitigation

Abstract: Background HIV screening (i.e. antigen/antibody) tests are followed by a supplemental (i.e. antibodyonly) if the screen is positive. Discrepant results can result from two scenarios: a false-positive screening test or acute HIV infection. These scenarios can be distinguished by a molecular HIV test, but due to contamination concerns, our laboratory recently implemented a policy requiring a second specimen dedicated for molecular HIV testing. Our objective was to (1) characterize the effect of this policy on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…12 A study evaluating the effects of requiring a dedicated sample for HIV NAT found a significant increase in the time between the screening test and HIV NAT. 13 Our results are in line with these previously published results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…12 A study evaluating the effects of requiring a dedicated sample for HIV NAT found a significant increase in the time between the screening test and HIV NAT. 13 Our results are in line with these previously published results.…”
Section: Discussionsupporting
confidence: 94%
“…A study evaluating the real-world performance of the current HIV testing algorithm in the United States found that 22% of testing encounters with a positive screening test and negative confirmatory test were incomplete because of lack of a sample for the HIV NAT 12 . A study evaluating the effects of requiring a dedicated sample for HIV NAT found a significant increase in the time between the screening test and HIV NAT 13 . Our results are in line with these previously published results.…”
Section: Discussionsupporting
confidence: 90%
“…Given the large volume of HIV screening tests performed, streamlined detection of true-positive HIV tests permitted growth of routine, opt-out HIV screening while allowing staff to prioritize contacting patients with true-positive results rather than tracking individuals with discordant results. It can be difficult to reach patients who require additional testing for HIV confirmation, and others may outright refuse to undergo further testing [ 14 , 15 ]. In fact, the limited number of unconfirmed discordant cases following implementation of reflex HIV-1 RNA testing resulted from insufficient sample (6–10 mL blood sample required) to perform the HIV-1 RNA assay and subsequent inability to make patient contact.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the limited number of unconfirmed discordant cases following implementation of reflex HIV-1 RNA testing resulted from insufficient sample (6–10 mL blood sample required) to perform the HIV-1 RNA assay and subsequent inability to make patient contact. In the absence of HIV RNA assay results, use of the signal-to-cutoff ratio of the screening assay may also mitigate this problem, which can help distinguish between false-positive and acute (true-positive) results before confirmatory testing is available [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%